التناول الإعلامي لمعركة طوفان الأقصى في برنامج الإذاعة الجزائرية - فرحات,وسيم; ذهب لعروسي,شريف; حشاني,عثمان (University of Eloued جامعة الوادي, 2024)
هدفت هذه الدراسة الى معرفة مدى تتناول القناة الإذاعية الأولى موضوع معركة طوفان الأقصى إعلاميا، وذلك بدراسة تحليلية على بعض نشرات السابعة مساءا للإذاعة الأولى، وذلك من 08 أكتوبر 2023 إلى غاية 11 جانفي 2024، كما تم الاعتماد على منهج تحليل المضمون، حيث تم الاعتماد على أداة استمارة تحليل المضمون، التي تمت من خلالها استخلاص نتائج الدراسة وهي: - ركزت القناة الإذاعية الأولى في تغطيتها الاخبارية على العديد من القضايا منها عمليات الاحتلال الصهيوني وعمليات المقاومة. - اعتمدت القناة الإذاعية الأولى في تغطيتها الاخبارية على العديد من المصادر أغلبها مصادر العربية. - الفاعلون البارزون الذين ركزت عليها القناة الإذاعية الأولى في تغطيتها الإخبارية هي هيئة مجلس الامن من ناحية الهيئات، أما الاشخاص فهم قادة المقاومة. - الضيوف الذين ركزت عليها القناة الإذاعية الأولى في تغطيتها الإخبارية هم الضيوف الفلسطينيين. - - الأشكال الصحفية التي ركزت عليها القناة الإذاعية الأولى في تغطيتها الإخبارية هي وردت القضية في عناوينها وتناولت القضية في وسط النشرة.. This study aimed to determine the extent to which the first radio channel addresses the topic of the Al-Aqsa flood battle in the media, Through an analytical study on some of 7 pm broadcasts of the first radio, from October 8, 2023 until January 11, 2024, The content analysis approach was also relied upon, where reliance was placed on The content analysis from tool, through which were drawn The study is: The first radio channel focused its news coverage on many issues, including operations the Zionist occupation and resistance operation. The first radio channel relied on many sources in new coverage, most of them … Arabic sources. The prominent actors that first radio channel focused on its news coverage are: In terms of bodies, The Security Council is the leaders of the resistance. The guests that first radio channel focused on it new coverage were the guests Palestinians. The journalistic forms that the radio channel focused on in its news coverage are received the issue was in its headlines and the issue was dealt with in the center of the bulletin
Keywords: معركةطوفان الأقصى; – القناة الإذاعيةالأولى; التناول الاعلامي; Al-Aqsa Flood Battle; First Radio Channel; Media coverage